Ilmu Hadits Dirayah Dan Riwayah: Kajian Komprehensif Tentang Dua Cabang Ilmu Pokok Dalam Studi Hadits Nabi Saw - Fauzan Asrofi; Dafa Al Fayad; Zikri Darussamin (CV. ITTC INDONESIA, 2026)
The science of hadith is a branch of Islamic science that holds a very important position in understanding Islamic teachings comprehensively. This article aims to examine two main branches of hadith science, namely the Science of Hadith Riwayah and the Science of Hadith Dirayah, along with their scope, objects of study, and urgency in contemporary Islamic studies. Through a library research approach, this article systematically describes the definition, history of development, methods, and contributions of both sciences to the authenticity and understanding of the Sunnah of the Prophet Muhammad SAW. The results of the study indicate that the Science of Hadith Riwayah focuses on the aspects of transmission and preservation of hadith texts, while the Science of Hadith Dirayah emphasizes criticism of the sanad and matan to determine the level of authenticity of the hadith. Both are complementary and inseparable in the effort to understand and practice the Sunnah of the Prophet Muhammad SAW correctly and authentically